ANALISIS PENGARUH KOMITMEN ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT. Madu Baru Bantul Yogyakarta) - Dadie, Camela Ikey Badhoeg; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2016)
This research is motivated by the presence of problems of the many employees who left the company at PT Madu Baru Bantul, Yogyakarta. Moreover, according to the pre-survey interviews that have been done, there is a lack of communication between the leaders with employees. Objective of this study was to analyze the influence of organizational commitment, leadership, employee performance, and job satisfaction as intervening variables in PT Madubaru Bantul Yogyakartace. Method of analysis of the data used in this research is descriptive and quantitative. The samples in this study were employees of PT Madubaru amounted to 77 people. Data collection was carried out by using a questionnaire that has been tested for validity and reliability. Data analysis method was using classic assumption test, path analylisis, as well as the coefficient of determination. Descriptive analysis shows that organizational commitment, leadership, job satisfaction and employee performance was moderate. Based on the results of multiple linear analysis and test of Sobel test indicates that organizational commitment, leadership, positive influence on employee performance and job satisfaction mediate organizational commitment and leadership on employee performance. The coefficient of determination shows that the work satifaction of PT Madubaru Bantul Yogyakarta are influenced by organizational commitment, leadership and job satisfaction by 32.o%, while the remaining 68,0% are influenced by other variables in which the research did not examined in this study. The coefficient of determination shows that the employees performance of PT Madubaru Bantul Yogyakarta are influenced by organizational commitment, leadership and job satisfaction by 47,7%, while the remaining 52,3% are influenced by other variables in which the research did not examined in this study